In the kitchen - Canizares, Susan (New York : Scholastic, 1999)
Photographs and simple text explore what happens in the kitchen, including peeling, mixing, cracking, and cooking.
Keywords: Cookery -- Juvenile literature; Kitchen -- Juvenile literature